Factors influencing the potential of rafting dispersal - analysis of patterns and causal mechanisms along the geographic range of intertidal species on the coast of Chile - López Arriagada, Boris Alejandro (2018)
Several studies, using both molecular and ecological evidence, confirm that rafting contributes to population connectivity and range expansion of many species. However, there is also indication that the effectiveness of rafting transport of species to establish in new habitats is limited. This suggests that transport might not be the limiting factor for the dispersal of species but that other factors (ecological or physiological) may restrict the colonization potential of these species. Also, this effective dispersal of a species could vary within its geographic range. The aim of this study was to assess the dispersal patterns of the floating bull kelp Durvillaea antarctica (Chamisso) Hariot 1892 and its associated epibionts along the continental coast of Chile (28°S-42°S) as well as to examine which mechanisms affect dispersal and connectivity of their populations within the geographic range of the continental clade of D. antarctica. It was proposed that ecological factors are more important in the effective dispersal of individuals of D. antarctica in central populations of its geographic range, while in peripheral populations reproductive and functional characteristics of the species are more important; deviations from the predictions of the effective dispersal within the geographic range could be due to local oceanographic conditions. The spatio-temporal variability of stranded bull kelps on beaches (Chapter 1), showed that strandings and morphometric characteristics of rafts varied strongly according to biogeographic districts along the coast of Chile during three consecutive years. The bimonthly study of strandings on three beaches (32°S, 36°S and 39°S) during three consecutive years (Chapter 2) confirmed the spatial pattern that higher stranded biomasses were observed in northern and southern beaches than central beaches. Furthermore, there was a strong seasonal pattern of kelp strandings that was also related to the intensity of local storms. A large-scale survey of rafted holdfasts (28°S-42°S) and a ...